Can small firms' perceived constraints help explain survival rates? - Seán Lyons (The Economic and Social Research Institute (ESRI), 2007)
Survey evidence on small firms' perceived constraints might provide useful information on the effects of institutional impediments, such as regulatory burdens, on post-entry performance. Using a new dataset that merges ENSR survey data on small firms' major constraints with Eurostat small firm demography data, we find that some perceived constraints are associated with significant differences in survival rates for new small firms. However, the constraints variables seem only weakly related to survival, and some prominent constraints including administrative regulations and availability of finance are not significant. We suggest refinements in survey design that might improve the usefulness of such data for inter-country comparisons.
Keywords: 330; Unternehmensentwicklung; Institutionelle Infrastruktur; Klein- und Mittelunternehmen; Schätzung; Europa